Empowering Refugees Through Psychosocial Support: Insights from the QFFD Clinic Counseling Services in Malaysia - A Y, Yahaya; M S, Raihanawati; A G, Nathirah (International Journal of Human and Health Sciences (IJHHS), 2025)
This paper presents an overview of the counseling services provided at the QFFD Clinic, a charitable healthcare initiative run by the Islamic Medical Association of Malaysia’s Response and Relief Team (IMARET) for refugees in Malaysia. The clinic, located in Selayang, Selangor, and Kota Tinggi, Johor, serves a diverse refugee population, with the majority of patients originating from Myanmar (86%). In 2023, a total of 231 counseling sessions were conducted, of which 191 were females and 40 were males. The counseling service is managed by an in-house certified counselor and addresses a range of issues faced by the refugee community. The primary reasons for seeking counseling include psychoeducation, mental health concerns, family-related issues, physical health problems, gender-based violence, financial challenges, and substance use. These challenges often intersect, highlighting the complex nature of their lived experiences as refugees in Malaysia. This presentation aims to highlight the key findings from the counseling services provided in 2023, with a focus on understanding the specific needs of refugee populations and the role of psychosocial support in promoting their overall well-being. It also explores the impact of gender differences on the utilization of services and the importance of culturally sensitive approaches in addressing mental health and social issues within this marginalized group. Through this analysis, we seek to emphasize the critical role of counseling in humanitarian healthcare settings and propose recommendations for enhancing the support provided to refugees in Malaysia. International Journal of Human and Health Sciences Supplementary Issue 01: 2025 Page: S37